Consumer Behaviour, Ecommerce,and Purchase IntentionTowards Brands:The Mediating Role of Consumer Attitude in UAE's online Market - AL SUDANI, MARWA (2025)
This research explores the complex relationships between consumer behaviour, e-commerce, consumer attitude, and purchase intention towards brands within the UAE's online market. Drawing on established consumer behaviour theoretical frameworks, the study intends to comprehend how consumer behaviour and e-commerce influence purchase intention towards brands, with a particular emphasis on the mediation of consumer attitude. The research seeks to shed light on the dynamics shaping consumer decisions in the UAE’s evolving digital marketplace, offering insights into how businesses can navigate e-commerce effectively. The study employed a structured questionnaire, adapted from previously validated measurement scales, to gather data from 454 participants in the UAE. The data was analysed using structural equation modelling (SEM) to test the relationships between consumer behaviour, e-commerce, consumer attitude, and purchase intention towards brands. The measurement model was tested to ensure the reliability and validity of the constructs, with satisfactory results confirming the robustness of the model. The structural model was subsequently used to evaluate the hypothesised relationships, providing empirical evidence on the association between the studied variables. The findings reveal several important insights into the UAE's online consumer market. Consumer behaviour and consumer attitude were found to have a significant direct impact on purchase intention towards brands, highlighting the importance of understanding consumer preferences and perceptions. Interestingly, the direct effect of e-commerce on purchase intention towards brands was insignificant. However, the e-commerce demonstrated a significant indirect impact on purchase intention towards brands through consumer attitude, indicating that consumer perceptions of the digital environment play a crucial role in their purchasing decisions. This highlights the importance of fostering positive consumer attitudes to leverage the potential of e-commerce. The study offers actionable implications for policymakers and marketers in the UAE. It highlights the importance of understanding consumer attitudes and creating positive perceptions to drive purchasing behaviour. It recommends that marketers focus on developing digital platforms that enhance consumer attitudes by integrating personalized experiences, social proof elements, and reputation management strategies. Leveraging data analytics to tailor digital interactions and build trust is crucial for driving consumer engagement. Policymakers are encouraged to support initiatives that promote a favourable e-commerce. Overall, in practical and policy terms, the study highlights the need for both businesses and regulators in the UAE to prioritize strategies and frameworks that strengthen consumer attitudes, as this is central to harnessing e-commerce’s full potential for sustainable market growth and competitiveness. Keywords: consumer behaviour, e-commerce, consumer attitude, purchase intention towards brands, online market